Public financial management reform in South African provincial basic education departments - Ajam, Tania; Fourie, David J. (2016)
Since the transition to democracy in 1994, the South African government has engaged in a sustained programme of public financial management (PFM) reform across the national, provincial and local spheres of government. This study evaluates the progress of the nine provincial education departments (PEDs) in implementing the Public Finance Management Act of 1999 and explores the factors that facilitated or impeded reform. A PFM progress (PFMP) index is constructed to track each PED's performance from 1997/1998 to 2013/2014 and then used to benchmark its progress over time and relative to the education sector as a whole. The indicators comprising the PFMP index assess key PFM functions (budgeting, accounting, financial auditing and audits of performance information), financial leadership and the effectiveness of governance institutions such as audit committees. While there has been considerable progress in PFM, distinct differences in the quality and effectiveness of PFM practices across the nine PEDs remain. Stable top administrative leadership, availability of PFM skills, varying degrees of accountability and departmental capacity to establish PFM systems that conform to new accounting standards drive variances in reform outcomes. - Reproduced.
Keywords: Basic Education - South Africa; Financial administration - South Africa; Financial administration